Гуманізація вищої освіти України в контексті Болонського процесу - Рижак, Л. (Соціогуманітарні проблеми людини, 2008)
Розглянуто тенденції гуманізації вищої освіти України в умовах євроінтеграції на засадах Болонської угоди. З’ясовано, що процес "університезації" та комерціалізації вищої освіти в рамках інформаційного суспільства розширює доступ до якісної освіти. Доведено, що гуманістичними вимірами освіти є її демократичність, відкритість і варіативність, у межах яких відбувається становлення компетентно творчої особистості. Tendencies of humanizing of Higher education of Ukraine in the conditions of Eurointegration in terms of the Bologna agreement are considered. It is found out that the process of "universatization and commercialization of Higher education in terms of informational society enlarges the access to a qualified education. It is proved that democratization, openness and variation in the limits of which the becoming of a competence-creative personality occurs, are humanizing measurements of education.